Primary empty sella syndrome-caused rhabdomyolysis misdiagnosed as recurrent sepsis: a case report and literature review. (May 2023) - Yu, Dongxu; Shi, Leilei; Zhang, Xinrui; Yang, Huifen; Feng, Jing; Wang, Yubao
Highlights: Rhabdomyolysis can present with a sepsis-like manifestation. Rhabdomyolysis may be a result of a rare cause - empty sella syndrome. Elevated procalcitonin levels may occur under noninfectious inflammatory conditions. Abstract : We reported a case of a 68-year-old man who presented with recurrent fever and multiorgan dysfunction. His significantly elevated procalcitonin and C-reactive protein levels indicated recurrent sepsis. However, no focus of infection and no pathogens were identified through a variety of examinations and tests. Although the increase of creatine kinase was less than five times the upper limit of normal value, the diagnosis of rhabdomyolysis secondary to adrenal insufficiency resulting from primary empty sella syndrome was finally made, as supported by serum myoglobin elevation, serum cortisol, and adrenocorticotropic hormone deficiency, bilateral adrenal atrophy on computed tomography, and empty sella on magnetic resonance imaging. After the glucocorticoid replacement treatment, the patient's myoglobin gradually returned to normal range, and his condition continued to improve. Rhabdomyolysis resulting from a rare cause may be misdiagnosed as sepsis in patients who present with increased procalcitonin levels.